Localizing Transformational Leadership: A Case of Indonesia - Murniati, Juliana; Panggabean, Hana; Tjitra, Hora (UI Scholars Hub, 2018)
Contemporary leadership studies recognize the influence of cultural context in leadership behavior. In line with the works, this study aims at putting the transformational leadership into a specific cultural context. This study applies the concept of Indonesian culture standard (Panggabean, Tjitra, Murniati, 2014) in particular a culture specific Indonesian leadership style termed as The Facilitating Leadership. We analyze two case studies of Indonesian leaders in profit organization and government institution with qualitative grounded theory. The result reveals a culture-specific form of transformational leadership, that is the transformational leadership behavior combines with facilitating leadership behavior. Three primary features are identified, namely idealistic influence based on populist commoner charisma; individualized consideration with Bapakism personal caring and support, and inspiring motivation by applying implicit communication. A mixture between transformational leadership approach with transactional goal setting and target attainment is found in government institution. Significant contribution of two primary characteristics of Indonesian culture standard is indicated, namely Multiculturality and Implicit Communication style. Based on the result, the study suggests to take into consideration cultural contexts in developing leadership development program.